Evolution of Achievement of Educational Progress During the Years of Independence of Uzbekistan - Ulugbekovich, Jumaniyazov Farkhod (PT. Antis International Publisher, 2024)
The development of the educational system during the years of independence of the Republic of Uzbekistan was aimed at creating a modern, accessible and high-quality education system that would contribute to the development of the individual and society. A socio-philosophical analysis of this evolution allows us to see the relationship between changes in education and the goals of social development, as well as the philosophical principles underlying the country's educational policy. The topic of educational development always remains relevant for any country, including Uzbekistan. Education plays an important role in social and economic development, as well as in shaping the future generation and training human resources.